The association of household socioeconomic status, neighbourhood support system and adherence to cardiovascular fitness among persons with diabetes mellitus in Ghana a hospital-based cross-sectional study - Doglikuu, Dominic (Research Journal in Medical and Health Sciences, 2023)
Diabetes mellitus (DM) is an independent risk-factor for cardiovascular diseases, and Physical Activities (PA) is known to reverse this risk-factor. However, some human attributes could influence adherence to PAs. This study therefore, investigates the association of household-socioeconomic-status (SES), neighborhood-support-system and adherence to PAs among persons with DM in Ghana. Facility-based cross-sectional-study was conducted among 530 T2DM patients in Ghana. Structured-questionnaires were used to collect socio-demographic, anthropometric, and clinical variables. SES was assessed using composite-wealth index and adherence to PAs was assessed using WHO PA-short form questionnaires. SPSS version-22 was used to analyse the data. At the end of the study, we found significant mean difference in low (P = 0.010) and high (P = 0.0001) social supports according to residential status. After we adjusted for age and diabetes duration, High-SES (quintile 3) Adjusted Odd Ratio (AOR) =0.68, 95% confidence interval (95%CI) (0.22, 0.07), Moderate-SES (quintile 3), AOR=3.16, 95%CI (1.01, 9.89) and High-social support system (quintile 2) AOR =3.29, 95%CI (1.02, 10.58) were significantly associated for adherence to PA. Low-SES (quintile 3) AOR= 3.52, 95%CI (1.44, 8.59) and low social support system (quintile 1) AOR=1.05, 95%CI (1.05, 1.09) were significant for adherence to sedentary-lifestyle. This study therefore concludes that SES, and Social-support systems maybe associated with adherence to PA. Clinicians should prioritized these variables as modifiable-factors in diseases preventions and health promotion